Biblical Courtship and Spiritual Entities: An Exegesis of Philippians 2:3-4 - Adeoye, Moses Adeleke (Universitas Pendidikan Ganesha, 2023)
The relationship between biblical courtship and spiritual entities is multifaceted and interconnected. In Christian courtship, this means being mindful of the other person's needs and desires and working together to build a relationship that is centered on mutual respect and support. The focus of this paper is to analyze Philippians 2:3-4 and examine the relationship between biblical courtship and spiritual entities. This research uses a descriptive method. Data collection in this research as primary data uses document analysis and also supported by secondary data from previous research. Data analysis process is through classifications, interpretation, compare the data, and analyze the context and meaning. The result found exegesis of Philippians 2:3-4 provides valuable guidance for Christian courtship by embracing humility, selflessness and spiritual practices to cultivate the qualities necessary for a healthy and loving relationship with another person. Biblical courtship would prioritize empathy, compassion, communication, practicing forgiveness, seeking to understand and meet the needs of one's partner. Spiritual entities provide guidance and tools for individuals to cultivate a deeper relationship with God and their partners by cultivating a deep and abiding relationship with God and prioritizing spiritual disciplines such as prayer, Bible study and worship. By incorporating these practices and principles into courtship, couples can build a strong foundation for a lifelong, Christ-centered relationship. In conclusion, biblical courtship should be grounded in a biblical worldview with individuals seeking to align their values and priorities with those of Christ.